INVIGORASI BENIH PADI GOGO LOKAL UNTUK MENINGKATKAN VIGOR DAN MENGATASI PERMASALAHAN DORMANSI FISIOLOGIS PASCAPANEN - SUTARIATI, GUSTI AYU KADE; ZUL’AIZA, ZUL’AIZA; DARSAN, STEFANY; ALI KARSA, LD MUHAMMAD; WANGADI, SRI; MUDI, LA (Jurnal Agroteknos, 2014)
The objective of this research was to evaluate the effect of seed invigoration on improving seed viability and vigor, and to overcome problems of postharvest physiological dormancy of upland rice seed. The research was conducted from February to June 2011 at Agrotechnology Laboratory, Faculty of Agriculture, Halu Oleo University. The experiment used randomized complete design which consisted of 13 treatments, i.e control (G0), Hidration-Dehidration (G1), Matriconditioning using ground brick (G2), Matriconditioning using ground burned-rice husk (G3), Bacillus CKD061 (G4), P. fluorescens PG01 (G5), Serratia CMN175 (G6), Biomatriconditioning using ground brick + Bacillus CKD061 (G7), Biomatriconditioning using ground brick + P. fluorescens PG01 (G8), Biomatriconditioning using ground brick + Serratia CMN175 (G9), Biomatriconditioning using ground burned-rice husk + Bacillus CKD061 (G10), Biomatriconditioning using ground burned-rice husk + P. fluorescens PG01 (G11), Biomatriconditioning using ground burned-rice husk + Serratia CMN175 (G12). Each treatment was replicated three times, therefore, overall there were 36 experimental units. Data obtained were analyzed using analysis of variance and followed with Duncan’s Multiple Range Test. The research results showed that bio-invigoration treatments integrated with rhizobacteria were effective to overcome the problems of postharvest physiological dormancy when local upland rice seeds were harvested. In addition, this treatment was also able to increase viability and vigour of the seed. Among treatments tested, the use of Bacillus sp. CKD061 or P. fluorescens PG01, either independently or integrated with matriconditioning using ground brick or ground burned- rice husk was more effective in improving viability and vigour of local upland rice seed compared to other treatments.